2015
DOI: 10.1073/pnas.1507782112
|View full text |Cite
|
Sign up to set email alerts
|

DDT-based indoor residual spraying suboptimal for visceral leishmaniasis elimination in India

Abstract: Indoor residual spraying (IRS) is used to control visceral leishmaniasis (VL) in India, but it is poorly quality assured. Quality assurance was performed in eight VL endemic districts in Bihar State, India, in 2014. Residual dichlorodiphenyltrichloroethane (DDT) was sampled from walls using Bostik tape discs, and DDT concentrations [grams of active ingredient per square meter (g ai/m 2 )] were determined using HPLC. Pre-IRS surveys were performed in three districts, and post-IRS surveys were performed in eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 27 publications
3
98
0
Order By: Relevance
“…Recently, Coleman et al [53] reported spraying of DDT (1gm/m 2 ) on walls up to 84.9 % and concluded that DDT-based IRS is suboptimal for achieving the goal of VL elimination.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Coleman et al [53] reported spraying of DDT (1gm/m 2 ) on walls up to 84.9 % and concluded that DDT-based IRS is suboptimal for achieving the goal of VL elimination.…”
Section: Resultsmentioning
confidence: 99%
“…if asymptomatics are not responsible for maintaining transmission). It also potentially explains why current control programmes in the ISC have been successful despite the apparent ineffectiveness of vector control (Coleman et al, 2015). Results from this model suggest that a diagnostic test with only 50% sensitivity might result in a considerable reduction (halving) of R 0 and offer the potential for elimination.…”
Section: Humans 411 Diagnosticsmentioning
confidence: 95%
“…In India, resistance of P. argentipes to DDT and pyrethroids is patchy (Ostyn et al, 2008;Dinesh et al, 2008b). The Indian and Nepalese routine IRS activities are considered suboptimal due to financial and logistical constraints, poor quality spraying practices and low community compliance (Chowdhury et al, 2011;Picado et al, 2012;Coleman et al, 2015). In Brazil, spraying lambda-cyhalothrin in animals sheds where the vector Lu.…”
Section: Vector Controlmentioning
confidence: 99%
“…However, there was slow reduction in vector density and development of resistance occurred in the targeted sandfly species due to substandard IRS spraying. 13 Personal protection methods, such as long-lasting insecticide-treated nets, N,N-diethyl-1, 3-methylbenzamide/neem oil, and chemical inhibition of feeding, resulted in up to 90% reduction in sandfly density. Control methods based on environmental management strategies included reduction in sandfly breeding sites and interruption of breeding using pheromone.…”
Section: Existing Modalities and Gaps In Vl Control And Eliminationmentioning
confidence: 99%